HUBUNGAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN AKHLAK SISWA KELAS X MA HIDAYATUL MUBTADIIN KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Siti Surnawati (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
Teacher competence is a basic demand for a person who carries out his professional duties as an educator. To achieve educational success, the education system must be organized and designed by people who are experts in their field, which is characterized by competence as a requirement. Globally, teachers must have personal, professional, and social competencies. Teachers must have knowledge, skills and skills as well as a more reliable and adequate attitude so that they are able to manage the teaching and learning process effectively and efficiently. This research is focused on the professional competence of teachers, namely on teaching skills. The population in this study was the entire teacher council of X MA Hidayatul Mubtadiin Regency, which numbered 15 teachers. Given that the total population is not more than 100 then 15 teachers are taken all as objects of study. The purpose of holding the study is to find out whether there is a significant relationship of competence with the teaching skills of X MA Hidayatul Mubtadiin Regency for the 2022/2023 Academic Year, to improve the Competence of X MA Hidayatul Mubtadiin Teachers and to improve the quality of teacher teaching skills at X MA Hidayatul Mubtadiin. Based on the results of the analysis "There is a significant relationship between teacher competence and teaching skills of X MA Hidayatul Mubtadiin, Academic Year 2022/2023", with evidence r count 0.717 > r table 0.514. The competence of X MA Hidayatul Mubtadiin is relatively high with an average score of 67.00 out of a maximum score of 80. Teachers' teaching skills are high, reaching an average score of 71.33